5.1k views
2 votes
3.3^(2x+1)-103^x+1=0 need value of x

User Korvinko
by
4.8k points

1 Answer

1 vote

Answer:

The value of
x is approximately -1.531.

Explanation:

Let
3.3^(2\cdot x + 1)-103^(x+1) = 0, we proceed to solve this expression by algebraic means:

1)
3.3^(2\cdot x + 1)-103^(x+1) = 0 Given

2)
3.3^(2\cdot x)\cdot 3.3 -103^(x)\cdot 103 = 0
a^(b)\cdot a^(c) = a^(b+c)

3)
(3.3^(x))^(2)\cdot 3.3 -\left[\left( √(103) \right)^(2)\right]^(x)\cdot 103 = 0
(a^(b))^(c) = a^(b\cdot c)

4)
(3.3^(x))^(2)\cdot 3.3 - \left[\left(√(103)\right)^(x)\right]^(2)\cdot 103 = 0
(a^(b))^(c) = a^(b\cdot c)/Commutative property

5)
\left[\left((3.3)/(√(103))\right)^(x)\right] ^(2)-(103)/(3.3) = 0 Existence of multiplicative inverse/Definition of division/Modulative property/
a^(b)\cdot a^(c) = a^(b+c)

6)
\left((3.3)/(√(103)) \right)^(2\cdot x)=(103)/(3.3) Existence of additive inverse/Modulative property/
(a^(b))^(c) = a^(b\cdot c)

7)
\log \left((3.3)/(√(103)) \right)^(2\cdot x)=\log (103)/(3.3) Definition of logarithm.

8)
2\cdot x\cdot \log \left((3.3)/(√(103)) \right)= \log (103)/(3.3)
\log_(b) a^(c) = c\cdot \log_(b) a

9)
2\cdot x \cdot [\log 3.3-\log √(103)] = \log 103 - \log 3.3
\log_(b) (a)/(d)

10)
x\cdot (2\cdot \log 3.3-\log 103) = \log 103 - \log 3.3
\log_(b) a^(c) = c\cdot \log_(b) a/Associative property

11)
x = (\log 103-\log 3.3)/(2\cdot \log 3.3-\log 103) Existence of multiplicative inverse/Definition of division/Modulative property

12)
x \approx -1.531 Result

The value of
x is approximately -1.531.

User Chanzerre
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.